Alys Bentley's Dance Impulse, Embodied Learning, and the Dancing Mind. Issue 3 (1st September 2016) - Saumaa, Hiie
ABSTRACT: The work and writings of Alys Bentley (1869–1951), an influential educator of dance and music, have been overlooked in dance scholarship. This article seeks to place Bentley in the history of dance in the United States, particularly in the context of early twentieth-century "natural" or expressive movement forms and Dalcrozean eurhythmics. The essay examines Bentley's legacy as a dance educator, her theoretical writings on movement and music education, and her views on dance, technique, and practice as expressed in her work of experimental poetry, The Dance of the Mind .